The Evaluation of Expanded Uncertainty of DC Voltages in the Presence of Electromagnetic Interferences using the LabVIEW Environment (Measurement Science Review, 2021)
The paper presents a possible application of integrated LabVIEW environment to the final evaluation of measurement results in direct measurement. The possibilities of presenting and visualizing the uncertainty of measurement results in a convenient and user-friendly form are also discussed. The topics discussed in the paper were presented using a developed application in LabVIEW. The paper discusses the topic of measurement of direct voltages in the presence of strong electromagnetic interferences. These problems are frequently omitted or hardly emphasized. It presents a suitable measuring system, a virtual measuring instrument created in the LabVIEW environment, and the results of tests carried out for an example NI PCI-6221 data acquisition board. The described approach can be applied also in other measurement situations.